2005
DOI: 10.1007/s11031-005-7955-3
|View full text |Cite
|
Sign up to set email alerts
|

The Distress Tolerance Scale: Development and Validation of a Self-Report Measure

Abstract: Trends in college binge drinking during a period of increased prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,367
6
28

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,295 publications
(1,544 citation statements)
references
References 34 publications
47
1,367
6
28
Order By: Relevance
“…To capture individual personality traits, the following measures were given during the screening session: the Distress Tolerance Scale, a reliable and valid self-report measure of emotional distress tolerance (Simons and Gaher 2005), and The State-Trait Anxiety questionnaire (Spielberger 1983), which measures trait level anxiety. The Center for Epidemiological Studies Depression Scale (CES-D; NIMH) was administered prior to the smoking lapse task in order to assess for depressive symptomatology over the week preceding the experimental session (Radloff 1977).…”
Section: Distal Measuresmentioning
confidence: 99%
“…To capture individual personality traits, the following measures were given during the screening session: the Distress Tolerance Scale, a reliable and valid self-report measure of emotional distress tolerance (Simons and Gaher 2005), and The State-Trait Anxiety questionnaire (Spielberger 1983), which measures trait level anxiety. The Center for Epidemiological Studies Depression Scale (CES-D; NIMH) was administered prior to the smoking lapse task in order to assess for depressive symptomatology over the week preceding the experimental session (Radloff 1977).…”
Section: Distal Measuresmentioning
confidence: 99%
“…The summary suggests that the distress intolerance construct is represented by five distress intolerance constructs: uncertainty, ambiguity, physical discomfort, frustration, and negative emotion. Bardeen et al confirmed this summary based on a factor analysis of scores from subscales derived from the Intolerance of Uncertainty Index-Part A (Carleton, Gosselin, & Asmundson, 2010), the Intolerance of Uncertainty Scale (Buhr & Dugas, 2002), the Multiple Stimulus Types Ambiguity Tolerance-I (McLain, 1993), the Tolerance of Ambiguity Scale-12 (Herman, Stevens, Bird, Mendenhall, & Oddou, 2010, a revised version of RE-REFINING DISTRESS INTOLERANCE 4 Budner's (1962) 16-item version), the Somatosensory Amplification Scale (Barsky, Wyshak, & Klerman, 1990), the DIS (Schmidt et al, 2006), the FDS (Harrington, 2005), and the DTS (Simons & Gaher, 2005).…”
Section: Re-refining the Measurement Of Distress Intolerancementioning
confidence: 79%
“…McHugh and Otto (2012) were the first to comprehensively synthesize a number of distress intolerance measures. They tested whether distress intolerance is comprised of a single construct by analysing the latent factor structure of four measures, including the Anxiety Sensitivity Index (Peterson & Reiss, 1992), the Frustration Discomfort Scale (FDS; Harrington, 2005), the Discomfort Intolerance Scale (DIS; Schmidt, Richey, & Fitzpatrick, 2006), and the Distress Tolerance Scale (DTS; Simons & Gaher, 2005). Factor analysis of the subscales scores supported a single-factor latent structure.…”
Section: Re-refining the Measurement Of Distress Intolerancementioning
confidence: 99%
“…THIS scale is a self-assessment index for emotional distress tolerance that was designed by Simons and Gaher [6]. The items of this scale assess distress tolerance based on individual abilities to tolerate emotional distress, mental assessment of distress, attention to negative emotions, and regulative measures to sedate distress.…”
Section: Distress Tolerance Scale (Dts)mentioning
confidence: 99%
“…Distress tolerance is defined by person's ability in experiencing and tolerating negative emotional states [6]. Distress tolerance is an important structure in the development of new vision about mental disorders as well as prevention and treatment [7].…”
Section: Introductionmentioning
confidence: 99%